Creativity Techniques: Toward Improvement of the Decision Process - Summers, Irvin; White, David E. (Academy of Management Review, 1976)
Selected creativity techniques to improve the decision process are illustrated, their application to the decision process elaborated, and their contribution to organization performance hypothesized. Impediments to the use of creativity techniques are discussed and suggestions made to reduce the effects of those impediments.